Teknik Pembuktian Gratifikasi Seks dalam Tindak Pidana Korupsi - Chandra Darusman S; Ilka Sandela; Basri Basri; Adam Sani (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Gratification as part of the criminal act of corruption has undergone changes in form and mode. Gratification is not only interpreted as giving gifts in the form of money, goods, prizes, or commissions, interest-free loans, travel tickets, lodging facilities, tourist trips, free medical treatment, and other facilities, but also sexual services to state administrators or civil servants. This research is normative legal research and aims to examine sexual services as part of gratification and techniques of proving sexual services as part of gratification. The results of the study show that sexual services can be classified as a form of gratification and the technique of proof is used to prove whether or not all of the elements of Article 12B of Law Number 20 of 2001 concerning the Eradication of Corruption Crimes have been fulfilled or not by using a balanced reverse burden of proof system.